2008
DOI: 10.1038/sj.jid.5700937
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sp1 in Transcription of Human ATP2A2 Gene in Keratinocytes

Abstract: The ATP2A2 gene encodes Ca2+-dependent ATPase, the dysfunction of which causes Darier disease. In this study, we analyzed the promoter structure of the human ATP2A2 gene using primary normal human keratinocytes (NHK). Reporter assays showed that deletion of -550/-529, -488/-472, -390/-362, or -42/-21 resulted in a significant decrease in human ATP2A2 promoter activity. Electrophoretic mobility shift assay (EMSA) showed that Sp1 is a transcription factor that binds to the -550/-529 and -488/-472 regions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 37 publications
0
20
0
3
Order By: Relevance
“…1a) under conditions of 60–90% transfection efficiency (data not shown, and Takagi et al. 11 ). UVB treatment increased COX‐2 mRNA level to 10‐fold higher than without UVB, which was reduced by ∼70% in the presence of COX‐2 siRNA in a steady state.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…1a) under conditions of 60–90% transfection efficiency (data not shown, and Takagi et al. 11 ). UVB treatment increased COX‐2 mRNA level to 10‐fold higher than without UVB, which was reduced by ∼70% in the presence of COX‐2 siRNA in a steady state.…”
Section: Resultsmentioning
confidence: 79%
“…Although the mechanism of ATP2A2 downregulation by PGE 2 has not been revealed, the function of transcription factors may be affected by PGE 2 because COX‐2 suppressed ATP2A2 promoter activity. Previously, we found that the transcription factor Sp1 transactivated the ATP2A2 promoter 11 . The function of Sp1 was affected by Ca 2+ concentration, which regulated the nuclear localization of Sp1 in keratinocytes 10 .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations